Integrating Ideological Education into University English Curriculum: A Model for Fostering Global Citizenship (Journal of Education, Humanities, and Social Research, 2025)
The integration of ideological education and global citizenship principles into university English curricula has gained increasing attention in recent years. While traditional English programs primarily focus on linguistic proficiency and cultural awareness, they often overlook critical aspects such as ethical responsibility, social justice, and global engagement. This paper explores the potential benefits and challenges of embedding ideological education within language learning, proposing a model that enhances students’ critical thinking, ethical reflection, and global awareness. The study highlights the role of educators in fostering meaningful discussions, the importance of interdisciplinary curriculum design, and the necessity of assessment methods that evaluate both language competence and students’ ability to engage with global issues. Furthermore, it discusses implications for policymakers, curriculum developers, and educators, emphasizing the need for institutional support and pedagogical innovation. Future research directions are suggested, focusing on the effectiveness of various teaching methodologies, the impact on language acquisition, and cross-cultural comparisons. By incorporating ideological education into English curricula, universities can better prepare students for active and responsible participation in an interconnected world.